Anatomy teaching in problem-based learning curriculum: challenges and opportunities in the Kingdom of Saudi Arabia - Kausar, Naheed (Frontiers in Education, 2025)
Anatomy is the key to medical education, and this study examines the current landscape of anatomy education in Saudi Arabia medical colleges utilizing problem-based learning (PBL) curricula, with the goal of optimizing pedagogical approaches and content dissemination. This study consolidated insights from students, faculty, and institutional frameworks to underscore significant challenges. These include the curtailment of essential anatomical content, inadequate reinforcement across the curriculum, a dearth of formalized faculty training and language-associated impediment stemming from the use of English as the primary language of instruction. Such challenges could undermine the comprehensive anatomical knowledge necessary for ensuring clinical proficiency and patient safety. The suggested modification encompasses the incorporation of anatomy across all stages of medical, education specialized faculty training, and the adoption of pedagogies that are culturally and linguistically appropriate. This study recommends standardized core anatomy curriculum, faculty training to implement dual language instructional techniques and the Saudi association for anatomical sciences to adopt a more prominent leadership position to improve and collaborate anatomical education in the Kingdom. Resolving these challenges enhance student engagement and knowledge retention, thereby harmonizing anatomy education with the healthcare commands of Saudi Arabia and objectives of vision 2030. In conclusion, this analysis culminates in a recommendation for a systematic change aimed at fostering excellence in anatomy education.